Engineering mechanics. : V.2 : Dynamics - Meriam, J. L. (James L.); Kraige, L. G. (New York : John Wiley and Sons, 1998)
This book is divided into two parts: Dynamics of particles; and Dynamics of rigid bodies.
Keywords: Engineering; Mechanics; Dynamics; Applied; Dynamics; Mechanics, Applied